EFFECT OF DEXAMETHASONE AS AN ADJUVANT IN SUPRACLAVICULAR BLOCK IN ORTHOPEDIC PATIENTS UNDERGOING ELBOW, FOREARM AND HAND SURGERY - SHEIKH, NG; JAVED, HM; SHEIKH, MG; AVAIS, B; BUTT, Z; JAMSHAID, B (Biological and Clinical Sciences Research Journal, 2022)
Supraclavicular blocks in orthopedic patients are considered to be of utmost importance and significance for attaining optimal results. The procedure is considered to obtain muscle relaxation and maintain stable hemodynamics. Moreover, they provide extended post-operative analgesic effects with the least reported adverse effects. The current study observed dexamethasone’s effects as an adjuvant therapy along the conventional anesthetic drugs among orthopedic patients undergoing elbow, forearm and hand surgeries. This study was conducted at the Department of anesthesiology, Aziz Bhatti Shaheed teaching hospital Gujrat, Pakistan, from 1st June 2022 to 30th October 2022. A Sum of sixty (n=60) patients of age group 18-65 years was designated into groups A and B. One group was administered conventional anesthetic drugs, and the other group was administered dexamethasone as adjuvant therapy. Patients were observed for the onset of sensory blockade, motor blockade and duration of the sensory blockade and motor blockade with the help of the Lovett rating scale and sensory score. Findings of the study reported significant differences in the onset and duration of sensory and motor blockade among group B compared to group A. It reported the onset was faster in group B (p<0.05) and longer in duration in group B (p<0.05).Moreover, the visual analog score (VAS) score at 9 hours remained significantly lower among the group receiving adjuvant therapy. No adverse effects were reported among the patients receiving the therapy. The present study suspects the beneficial role of dexamethasone as adjuvant therapy for the group of patients. It concluded that the patients receiving the adjuvant therapy reported faster onset of sensory and motor blockade, which also lasted for longer. Therefore, dexamethasone is reported to have a prolonged anesthetic effect if administered as an adjuvant therapy among orthopedic patients.